Christian origins and Greco-Roman culture : social and literary contexts for the New Testament - Porter, Stanley E., 1956-; Pitts, Andrew W. (Texts and Editions for New Testament Study, 2013)
In Christian Origins and Greco-Roman Culture , Stanley Porter and Andrew Pitts assemble an international team of scholars whose work has focused on reconstructing the social matrix for earliest Christianity through the use of Greco-Roman materials and literary forms. Each essay moves forward the current understanding of how primitive Christianity situated itself in relation to evolving Hellenistic culture. Some essays focus on configuring the social context for the origins of the Jesus movement and beyond, while others assess the literary relation between early Christian and Greco-Roman texts.